2013
DOI: 10.1158/1078-0432.ccr-12-3003
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival with HPV among African Americans with Oropharyngeal Cancer

Abstract: Purpose A major limitation of studies reporting a lower prevalence rate of human papilloma virus (HPV) in African American (AA) oropharyngeal cancer (OPSCC) patients than Caucasian Americans (CA), with corresponding worse outcomes, was adequate representation of HPV positive AA patients. This study examined survival outcomes in HPV positive and HPV negative AA with OPSCC Experimental Design The study cohort of 121 primary OPSCC had 42% AA. Variables of interest included age, race, gender, HPV status, stage, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
95
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 39 publications
11
95
1
1
Order By: Relevance
“…Zandberg and colleagues present a survival analysis that was stratified by race and HPV tumor status. Consistent with previous reports (23,24), HPV-positive patients had improved survival as compared with HPV-negative patients after stratifying by race. However, when HPV-negative patients were stratified by race, there was a significant difference in overall survival.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Zandberg and colleagues present a survival analysis that was stratified by race and HPV tumor status. Consistent with previous reports (23,24), HPV-positive patients had improved survival as compared with HPV-negative patients after stratifying by race. However, when HPV-negative patients were stratified by race, there was a significant difference in overall survival.…”
supporting
confidence: 90%
“…In a recent survival analysis focusing on racial differences, blacks had significantly worse overall survival as compared with white patients with HPV-negative oropharyngeal cancer in a univariate analysis (24). However, race was not an independent marker for prognosis in multivariate models.…”
mentioning
confidence: 93%
“…In the United States (US), a clear disparity in HNC survival has been reported between Black and White patients, particularly for oropharyngeal cancers. Poor survival rates for Black Americans compared to White Americans have been observed (7), and some studies have suggested that this disparity may be explained at least partially by a difference in prevalence of HPV infection (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In our research we identify 15 articles focused on HPV associated oropharyngeal cancer and sexual behavior as a risk factor 1,3,9,[11][12][13][14][15][16][17][18][19][20][21][22] . One article studied the knowledge of HPV and its association with oropharyngeal cancer in a high-risk population 16 .…”
Section: Resultsmentioning
confidence: 99%
“…HPV related oropharyngeal squamous cell carcinomas have been showing a better prognosis if compared with those related to tobacco and alcoholism 9,10 . This fact makes stratification necessary for studies involving oropharyngeal squamous cell carcinomas.…”
Section: C) Hpv and Oropharyngeal Neoplasmsmentioning
confidence: 99%